The Double-Edged Sword of Immunosuppressive Therapy in Kidney Transplantation: A Rare Case Report of Pulmonary Mucormycosis Post-Transplant and Literature Review - Zhang, Hengcheng; Wang, Ke; Chen, Hao; Sun, Li; Wang, Zijie; Fei, Shuang; Tan, Ruoyun; Gu, Min (Frontiers in Medicine, 2020)
Immunosuppressive therapy is improving the graft survival of kidney transplant recipients and increasing the potential risk of infection. Pulmonary mucormycosis is a rare post-operative infection complication characterized with rapid deterioration and high mortality. In this case, a 33-year-old patient underwent a kidney transplantation with regular immunosuppressive therapy. Soon, 38 days post-transplant, pulmonary patchy shadows can be seen in the radiological examination and rounded into a large cavity formation with splenic rupture 25 days later. The diagnosis of mucormycosis was confirmed by lung biopsy and spleen histopathology. This case is a reminder that early diagnosis is imperative, meanwhile, rational antifungal therapy, timely elimination of immunosuppressants, and alternatively, abandoning the graft should be prudently assessed in the treatment of mucormycosis.